111k views
2 votes
11-1/2y=3+6x solve for y

User Nico
by
4.6k points

2 Answers

4 votes

So, since we have
11-(2)/(y)=3+6x, and we want to solve for y, that means we should first get y out of the denominator so we can manipulate it better, so multiplying the whole equation by y yields:


11y-2=y(3+6x)

So, now we want to bring all the ys to one side and the rest of the variables and constants to the other, that gives us:


11y-y(3+6x)=2

Factoring y out of the RHS gives us:


image

So, now we want to divide both sides by (-6x+8) to get y by itself:


image

With that we have solved for y.

User Shih
by
5.0k points
2 votes

11- \frac{1}{2} y=3+6x

Taking y to the other side;

11-3-6x= \frac{1}{2} y

8-6x= \frac{1}{2}y

Multiply each side by 2

16-12x=y

y=16-12x

User Steve Jorgensen
by
5.4k points